Prawna dopuszczalność rezygnacji z wybranych dochodów własnych gmin - Kowalczyk, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Local-governmental fees, especially those that are associated withan increase inproperty value, are and probably will continue to bean important form of a fiscal standpoint source of revenue for municipal budgets. So, current question remains at the nature charges still and entitlement of self-governed organ result from there. Hence thecontinued interest of representatives of both thescience and practiceissues are related to them.The publication raise done of the major problems associated with the assessment and collectionof fees, and for their obligatoriness. The problem is so complex that the construction standarizing these charges can be very varied, andthe legislature does not use the uniformand consistent definitions, which clearlylead to the conclusion that all revenues from the sefees are to betreated as a mandatory or their optionality may be decided by municipal body.
Keywords: gmina; dochody gminy; opłaty samorządowe; budżet gminy